Building Best Practice for Access to Born-Digital Records - Cobourn, Alston; Taylor, Ashley (My University, 2018)
Archivists have spent the better part of the past two decades working to establish standards and best practices for acquiring, appraising, arranging, describing, and preserving digital archives. For many reasons, however, methods of providing access have been more difficult to define. In 2017, the Digital Library Federation (DLF) Born-Digital Access Working Group formed with the intention of both researching current methods and creating a community of practice surrounding these issues. With origins in working sessions at Society of American Archivists (SAA) annual meetings in 2015 and 2016, the group has built upon foundational research in order to facilitate defining best practices for born-digital access. Since the beginning of 2018, the group has focused on two primary objectives: proposing recommendations for implementing a leveled approach to various access-related activities, modeled on the National Digital Stewardship Alliance (NDSA)’s Levels of Preservation document; and researching the behavior and needs of users of born-digital resources. This report expands upon research presented at the 2018 SAA Research Forum, including group development, informing scholarship, initial steps and findings, and next steps for this ongoing project.
Presented at the 2018 Society of American Archivists Research Forum, Washington, D.C.
Keywords: Archives; Born-digital records